Diagnóstico geoecológico como base para el ordenamiento de un territorio: Parque Metropolitano de La Habana - Díaz García, S. (Geographicalia, 2016)
The development of the cities decrease the potencial of green areas. The population require that spaces for its amusement and recreation and also in order to be evident the esthetics and natural values. These aspects will be considered in the planning and management of those places that still keep environment value. According with those ideas the public administration of the city put up the Metropolitan Park of Habana. Its territory had been divided into units of landscape and studied by some gauges or index which allowed to establish the geoecological diagnostic of the territory and to program measures for its planning.
Keywords: green areas; esthetics and environmet values; landscape; geoecological diagnostic